Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Laptop Merek Dell di Kota Semarang (Studi Kasus Pada Konsumen Laptop Merek Dell di Kecamatan Banyumanik Kota Semarang) - Tamimi, Prana Sabrina; Nugraha, Hari Susanta; Widiartanto, Widiartanto (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Current condition of the laptop competition is very tight, so the company should make a strategy to achieve a higher market share. Laptops are one of the tool to meeting the needs of consumers in the field of technology and information. Dell is a company engaged in the information technology industry. The purpose of this study was to know the effect of brand image and product quality to the brand laptop Dell purchase decision. This type of research is explanatory research, the number of respondents are 100 peoples with purposive sampling technique. Data collection techniques in this study using questionnaires, interviews, and literature. The analytical method used is the validity, reliability, correlation coefficient, coefficient of determination, simple linear regression, t test, regression multiple linear, and F testBased on the analysis of the study variables of brand image and product quality has a positive influence on purchasing decisions. Quality variable of the products have the most impact which 56.3%. While the brand image variables have an effect of 46.7%. Taken together (simultaneously) variables brand image and product quality has a contribution of 59% of the purchase decision. In conclusion there is positive between the brand image and product quality to the Dell brand laptop purchase decision. Suggestions for improvement of purchasing decisions by improving product quality and pay more attention to deficiencies which can be obtained through consumer complaints. Besides maintaining a good brand image that is by keep in constant communication with consumers and provide a clearer information to attract the attention of consumers better.